Influence of aging on the color visual field in humans: A cross-sectional study. Issue 50 (17th December 2021) - Yada, Takeshi; Tokumaru, Osamu; Eshima, Nobuoki; Kitano, Takaaki; Yokoi, Isao
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Age-related narrowing of the visual field is observed in the elderly, which leads to reduced cognitive and psychomotor functions. The aim of the present cross-sectional study was to determine the influence of aging on the visual field for color vision in humans, with respect to angular thresholds for object detection and color detection. The subjects were divided into the elderly group (mean 76.1-year-old [70–89]) and the control group (25.2 [18–47]). Visual fields for different colors (blue, green, yellow, and red) were measured by manual kinetic perimetry and evaluated in terms of 2 measures of visual-field width: angular thresholds for object detection and those for color detection. While angular thresholds for object detection were significantly wider than those for color detection in the control group ( P  < .001), there was no difference in the elderly group ( P  = .06). Moreover, angular thresholds for object detection were significantly wider in the control group than in the elderly group ( P  = .019), but angular thresholds for color detection were not significantly different between the 2 groups ( P  = .903). The observed age-related changes in angular thresholds for object detection in color vision may reflect an age-related reduction in rod function. Stable cone function might explain the preserved angular thresholds for color detection in the elderly.